Money handling and obesity: a test of the exaptation hypothesis - Karve, Shraddha; Shurpali, Ketaki; Dahanukar, Neelesh; Paranjape, Sharayu; Jog, Maithili; Belsare, Prajakta; Watve, Milind (Current Science, 2011)
The food reward centres in the brain play a central role in the regulation of food intake and thereby obesity. In the modern lifestyle, a number of artificial rewards such as money have been introduced and brain areas evolved for handling food rewards appear to be exapted to handle money and other rewards. This implies that the changing behaviour related to these rewards could influence obesity. Considering money as a reward, we conducted a survey of 211 full-time cashiers to test whether ownership over cash, amount of cash handled and duration of cash-handling work correlated with obesity parameters. Body mass index was significantly affected by sex, ownership, amount of money handled and duration of cash-handling service. Waist-to-hip ratio was significantly affected by sex, amount of money handled and marginally by ownership. The results are compatible with the exaptation hypothesis. It is possible that increasing importance of non-food rewards may play a significant role in the obesity epidemic.
Keywords: Body weight; economics of obesity; exaptation hypothesis; money handling